2000
DOI: 10.1046/j.1469-8137.2000.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining uptake of ‘non‐labile’ soil cadmium by Thlaspi caerulescens using isotopic dilution techniques

Abstract: We assessed the ability of several populations of the metal-hyperaccumulator species, Thlaspi caerulescens, to mobilize non-labile cadmium in soils historically contaminated by Pb\Zn mine spoil or sewage sludge. . This suggests that, in the soils studied, T. caerulescens did not mobilize non-labile soil Cd by producing root exudates or altering rhizosphere pH. The results imply that there may be significant restrictions to metal bioavailability, even to hyperaccumulator species, in heavily contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 33 publications
(48 reference statements)
9
49
0
3
Order By: Relevance
“…Enabled by a high-affinity uptake mechanism for Zn in the roots, T. caerulescens can accumulate large amounts of Zn at a relatively constant rate from soil solution over a wide range of Zn concentrations (Pence et al, 2000). This trait is very typical for Zn hyperaccumulators , and has been reported many times before for different ecotypes of T. caerulescens (La Calamine and Le Prayon) originating from the north-east of Belgium (Assunção et al, 2003;Baker et al, 1994;Hutchinson (Table 4), as was mentioned previously, it was tested whether these soil solution properties should be taken into account in addition to the HM concentration in soil solution for predicting uptake of HMs by L. hartwegii and T. caerulescens. We used the following equation:…”
Section: Relationship Between Plant Uptake and Heavy Metal Concentratmentioning
confidence: 82%
“…Enabled by a high-affinity uptake mechanism for Zn in the roots, T. caerulescens can accumulate large amounts of Zn at a relatively constant rate from soil solution over a wide range of Zn concentrations (Pence et al, 2000). This trait is very typical for Zn hyperaccumulators , and has been reported many times before for different ecotypes of T. caerulescens (La Calamine and Le Prayon) originating from the north-east of Belgium (Assunção et al, 2003;Baker et al, 1994;Hutchinson (Table 4), as was mentioned previously, it was tested whether these soil solution properties should be taken into account in addition to the HM concentration in soil solution for predicting uptake of HMs by L. hartwegii and T. caerulescens. We used the following equation:…”
Section: Relationship Between Plant Uptake and Heavy Metal Concentratmentioning
confidence: 82%
“…Historically, isotopic dilution (ID) techniques were used initially to study the reactions, fixation and residual availability of fertilizer nutrients, particularly phosphorus and potassium, using radioisotopes of P and K. Subsequently these techniques have been used for TEs, for example Ni, Zn, Cd, Cd and As (for example [159][160][161][162][163][164]). Isotopic dilution techniques using radioisotopes of TEs allow examination of their partitioning into isotopically and nonisotopically exchangeable pools, which are described as labile and nonlabile, respectively.…”
Section: Isotopic Dilution Techniquesmentioning
confidence: 99%
“…As any other form or fraction of TEs in soils, exchange between labile and nonlabile pools occurs. In other words, nonlabile pool can be mobilized, for example following a change in soil pH and/or E h and reaction with plant root exudates organic compounds and their metabolites [161][162][163]165]. In essence, the partitioning of TEs using isotopic dilution methods is similar to SEPs but there are two major differences: (a) instead of fractionating TEs in several pools as in SEPs (for example exchangeable, bound to carbonates, organic matter and metal oxides), this fractionates them into two distinct pools, labile and nonlabile; and (b) being less intrusive and more or less direct measurements the ID techniques do not suffer from procedural artefacts as is common in SEPs.…”
Section: Isotopic Dilution Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that T. caerulescens extracts soil Cd from the same 'labile pool' as other plant species rather than extracting nonlabile forms [94][95][96][97]. Several researchers have reported that roots of some strains of T. caerulescens tend to grow into spots of soil with higher Zn or Cd contamination [98][99][100].…”
Section: Soil Cadmium Contamination Requiring Remediation To Protect mentioning
confidence: 99%